The Implied Equity Risk Premium: An Evaluation of Empirical Methods - David Schröder (University of Bonn, Bonn Graduate School of Economics (BGSE), 2005)
A new approach of estimating a forward-looking equity risk premium (ERP) is to calculate the implied risk premium using present value (PV) formulas. This paper compares implied risk premia obtained from dierent PV models and evaluates them by analyzing their underlying firmspecific cost-of-capital estimates. It is shown that specific versions of dividend discount models (DDM) and residual income models (RIM) lead to similar ERP estimates. However, the results of cross-sectional regression tests of individual firm risk suggest that there are qualitative dierences between both approaches. Expected firm risk obtained from the DDM is more in line with standard asset pricing models and performs better in predicting future stock returns than estimates from the RIM.
Keywords: G12; 330; equity risk premium; cost of capital; expected stock returns